Behavior of divertor and first wall armour materials at plasma heat fluxes relevant to ITER ELMs and disruptions. (August 2017) - Kovalenko, D.V.; Klimov, N.S.; Podkovyrov, V.L.; Kupriyanov, I.B.; Poresanov, N.P.; Zabirova, N.E.; Bazaleev, E.B.; Safronov, V.M.; Muzichenko, A.D.; Putrik, A.B.; Zhitlukhin, A.M.
Highlights: Plasma and photonic flux testing of W and Be were carried out on the QSPA facilities. Melt layer movement and the cracks formation are the main erosion mechanisms of W and Be under plasma stream impact. Corrugated structure are formed on the Be target surface after photonic flux testing Scaling equation for describing the influence of the conditions during the film deposition process on the D/W ratio was obtained Abstract: The paper presents the main results of numerous experiments carried out over the past 10 years at QSPA-T and QSPA-Be plasma guns in support of ITER. Special targets made of pure W, W-1%La2 O3 and two types of Be (TGP-56FW and S65-C) were tested under the series of repeated plasma stream and photonic flux impact. Maximum heat load on the target surface was up to 2.5 MJ/m 2 in the case of plasma testing and was equal to 0.5 MJ/m 2 in the case of photonic flux testing. Pulse waveform was rectangular with tpulse = 0.5 ms. It was found that the main erosion mechanisms of W and Be under plasma stream impact are the melt layer movement, the ejection of droplets and the cracks formation. As a result of repeated photonic fluxes a regular, "corrugated" structure are eventually formed on the Be target surface. Study of erosion products of W formed under plasma stream impact on the W target has shown that the D/W atomic ratio in the deposited W films during pulsed events may be the same or even higher than that for stationary processes.